Creating a Village Website as a Supporting Medium for Community Members’ Business Productivity - Ferri Wicaksono; Haryoko Haryoko; Novi Puspita Sari (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
The covid-19 pandemic has worsened the economy of the informal sector. Online media may serve as one solution for opening new business spaces. The main problem encountered by our partner is the lack of understanding and use of digital media as a means of promotion. This activity aims to facilitate the creation of a village website as a supporting medium to increase the productivity of the residents.The partner of this community service program is the community members of RT 01 RW 34 Padukuhan Banjeng, Kanoman, Maguwoharjo, Depok, Sleman. This activity employed the Participatory Rural Appraisal (PRA) method. The implementation of these community service activities have successfully increased four aspects of community members’ productivity: 1) human development, shown by the higher understanding and ability in using the website to promote their business and increase the value of their business products; 2) business development, demonstrated by the enthusiasm of seventeen business owners in adding content to the website and in giving access to community members to help develop their digital-based businesses; 3) environmental development, manifested in pictures of the village on the website to provide a good impression of the village; and 4) institutional development, illustrated by the initiation of a new institutional model to ensure the sustainable use of the website, as a digital media to promote the community members’businesses.